2002
DOI: 10.1076/chin.8.1.41.8717
|View full text |Cite
|
Sign up to set email alerts
|

Two Sets of Twins with Selective Mutism: Neuropsychological Findings

Abstract: Neuropsychological data are reviewed from two sets of dizygotic twins presenting with selective mutism characterized by situation specific anxiety, extreme passive behavior, lack of responsivity, lack of peer interaction, and a chronic course of selective mutism. Both sets of twins had a history of prematurity and delayed speech development. One set of twins presented with normal intelligence and normal receptive language skills but with expressive language and oral motor sequencing difficulties. The second se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…Subtle motor impairment and not anxiety alone may be one reason for withdrawal from some social situations in some children with SM. Furthermore, oromotor coordination deficits have been demonstrated in two pairs of twins with SM [Gray et al, 2002], and the most prevalent language disorder in SM is found to be articulation disorder [Kristensen, 2000], which also reflects motor problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subtle motor impairment and not anxiety alone may be one reason for withdrawal from some social situations in some children with SM. Furthermore, oromotor coordination deficits have been demonstrated in two pairs of twins with SM [Gray et al, 2002], and the most prevalent language disorder in SM is found to be articulation disorder [Kristensen, 2000], which also reflects motor problems.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, more comprehensive neuropsychological studies of SM are scarce. However, Gray et al [2002] have described results from two sets of dizygotic twins with SM. Both sets of twins were prematurely born.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in anxious adults presented with somewhat threatening auditory stimuli, only state anxiety but not trait anxiety influenced attention, as measured by event-related potentials (Mercado, Carretié, Tapia, & Gómez-Jarabo, 2006). Gray et al (2002) described an attentional test pattern indicative of what he calls an anxious response style in three of the four twins with SM he studied. This response style was characterized by slow reaction times, numerous omission errors (errors due to non responding) along with hardly any commission errors (false positive errors).…”
Section: The Relation Between Neuropsychological Measures and Questiomentioning
confidence: 98%
“…To our knowledge, neuropsychological test results from case-control studies have not been published, and it is not known whether behavioral ratings of attention deficits and anxiety co-vary in this patient group. However, a study including two twin pairs with SM revealed an attentional problem in three of the four twins on a continuous performance test (Gray, Jordan, Ziegler, & Livingston, 2002).…”
mentioning
confidence: 99%
“…Therefore, it is difficult to determine whether there is a distinct profile of deficits in children with SM or whether their developmental delays are comparable to those of other children with developmental delays but without SM. A review of case studies 27 suggests that articulation/phonological disorders can occur alone or in combination with receptive and/or expressive language delays. Of additional concern in SM is the development of higher level language and cognitive skills because lack of communication experience may significantly limit development of these skills, which support academic and social success.…”
Section: Developmental Delaysmentioning
confidence: 99%